Editorial: Observations on slums and their touristification - Burgold, Julia; Frenzel, Fabian; Rolfes, Manfred (DIE ERDE – Journal of the Geographical Society of Berlin, 2013)
Editorial to Issue 144 (2) of DIE ERDE: Slum tourism